2022
DOI: 10.1063/5.0100191
|View full text |Cite
|
Sign up to set email alerts
|

Highly sensitive and broadband photodetectors based on WSe2/MoS2 heterostructures with van der Waals contact electrodes

Abstract: A nanoscale photodetector is a crucial part of intelligent imaging and wireless communication devices. Building van der Waals (vdWs) heterostructures based on two-dimensional transition metal dichalcogenides is thought to be a smart approach for achieving nanoscale photodetectors. However, the pinning effect induced by surface states, defects, and metal-induced gap states during the fabrication process of vdWs heterostructures and contacting electrodes leads to a large Schottky barrier and consequently limits … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 44 publications
0
8
1
Order By: Relevance
“…(i) The inserted Gr layer was mechanically transferred onto the substrate, forming a VdW contact, which breaks the metal–semiconductor interaction and inhibits the propagation of states perpendicular to Gr . Moreover, 2D semimetal Gr has a limited electronic density of states (DOS) near the Dirac point; therefore, few MIGS are induced at the surface of the semiconductor. , Owing to these features, the MIGS, which mainly causes FL pinning, was reduced, leading to FL unpinning at the interface between the Gr and semiconductor. Furthermore, near the Dirac point, which is located ∼4.48 eV from the vacuum level, charge carriers show linear electronic dispersion, allowing carriers to act electron- and hole-like when the FL is above and below the Dirac point, respectively .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(i) The inserted Gr layer was mechanically transferred onto the substrate, forming a VdW contact, which breaks the metal–semiconductor interaction and inhibits the propagation of states perpendicular to Gr . Moreover, 2D semimetal Gr has a limited electronic density of states (DOS) near the Dirac point; therefore, few MIGS are induced at the surface of the semiconductor. , Owing to these features, the MIGS, which mainly causes FL pinning, was reduced, leading to FL unpinning at the interface between the Gr and semiconductor. Furthermore, near the Dirac point, which is located ∼4.48 eV from the vacuum level, charge carriers show linear electronic dispersion, allowing carriers to act electron- and hole-like when the FL is above and below the Dirac point, respectively .…”
Section: Resultsmentioning
confidence: 99%
“…Graphene (Gr) is a 2D semimetallic material composed of a single layer of carbon atoms. Although it is known to have a zero bandgap, in which the conduction and valence bands cross at the Dirac point, it can effectively suppress MIGS owing to the VdW contact. Furthermore, when Gr is in contact with the metal, a charge-sharing effect occurs from Gr to the metal, which aligns the FLs on both sides of the contact. Considering these features, Gr is a qualified interlayer candidate for a universal MIS contact structure suitable for both n- and p-type semiconductors.…”
Section: Introductionmentioning
confidence: 99%
“…To enhance the speed of the UV photodetector, band alignment technology is urgently needed to achieve high efficiency of photocarrier separation. In the type‐II band alignment heterostructure, [ 25 ] the photogenerated electron‐hole pairs can be separated at the interface spontaneously in a very short time of ≈50 fs. [ 26 ] The separation of photocarriers in space inhibits the photocarrier recombination enabling high photoresponsivity ( R ).…”
Section: Introductionmentioning
confidence: 99%
“…In this Letter, we experimentally report a broadband photodetector based on WSe 2 /MoS 2 vdWHs by simply using ITO electrodes as contact layers. Compared with our recent reports, 9,22) this type of device is free of the additional buffer layer to directly contact the semiconductor layers, which may avoid the additional resistance caused by DIGS to effectively enhance the photoelectric performance. The fabricated photodetectors can operate ranging from 405 to 1050 nm with the highest responsivity of 1392 mA W −1 and specific detectivity of 7.78 × 10 12 Jones (1 Jones = 1 cm Hz 1/2 W −1 ) at room temperature.…”
mentioning
confidence: 95%
“…11,14,17,18) Recent efforts have been devoted to improving photoelectric performances by optimizing the contact between 2DMs semiconductors and metal electrodes, including modulation of gate voltage, tuning of carrier behaviors, and introduction of a buffer layer. [19][20][21] In our previous works, 9,22) we demonstrated that graphene/indium tin oxide (ITO) hybrid electrodes could serve as a buffer layer for reducing the contact barrier in both bare TMDs and their vdWHs-based photodetectors. However, in these reported low-contact structures, the strict selection of a proper work function in the buffer layer is necessary.…”
mentioning
confidence: 99%